Recursos didácticos para la enseñanza de estudios sociales - Marcillo Tigselema, Diego Armando (2016)
The methodological strategies and influence learning processes in the area of social studies at the School of Basic Education "Six of March" is scarce, so it is planned this investigation in order to strengthen the learning process through the acquisition and optimum utilization of teaching resources in Social Studies to improve the level of academic instruction in students. In the process knowledge they are systematized and assimilated by students; not only from teaching standards, but from the integration of different factors must be achieved to put the student in contact with different patterns more complex expression that characterize the production of consistent teaching resources, reflective analysis of the same from models. Employment problems of teaching methods and resources when imparting new knowledge in social studies have an impact on the educational community that consists of teachers, students and parents; encouraging the active participation of the same so that they can interpret, operate and use in different situations of daily life. The method to be followed in this project is a documentary bibliographical research and field. The development of theoretical scientific basis is part of books, and the Internet that support in the formulation of the fundamental categories applies inquiry by analyzing surveys to demonstrate statistical hypothesis. This research will allow a proposal on the correct use of teaching resources when teaching the different subjects of Social Studies is structured, so that, in this way a valid and significant cognitive capture is achieved.